2020
DOI: 10.1021/acschembio.0c00755
|View full text |Cite
|
Sign up to set email alerts
|

A Bump-Hole Strategy for Increased Stringency of Cell-Specific Metabolic Labeling of RNA

Abstract: Profiling RNA expression in a cell-specific manner continues to be a grand challenge in biochemical research. Bioorthogonal nucleosides can be utilized to track RNA expression; however, these methods currently have limitations due to background and incorporation of analogs into undesired cells. Herein, we design and demonstrate that uracil phosphoribosyltransferase can be engineered to match 5-vinyluracil for cell-specific metabolic labeling of RNA with exceptional specificity and stringency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The potential to use this novel catalyst in advanced organic synthesis is highlighted by the fact that compounds 2r and 2s have been successfully formed from important drug molecules without affecting other functionalities. Here, 2s is a particularly interesting product as its equivalent alkyne ( 1s ) was in the top 200 highest grossing drugs in 2020 under the name Mirena, , while 1r is a component of the urology drugs Yaz and Lo Loestren. , Finally, product 2t , which is a component of an RNA biomarker as well as antiviral , and anticancer agents, was prepared in a straightforward manner. The starting material 1t was not soluble in acetonitrile, but performing the reaction in water allowed the formation of 2t in an 81% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The potential to use this novel catalyst in advanced organic synthesis is highlighted by the fact that compounds 2r and 2s have been successfully formed from important drug molecules without affecting other functionalities. Here, 2s is a particularly interesting product as its equivalent alkyne ( 1s ) was in the top 200 highest grossing drugs in 2020 under the name Mirena, , while 1r is a component of the urology drugs Yaz and Lo Loestren. , Finally, product 2t , which is a component of an RNA biomarker as well as antiviral , and anticancer agents, was prepared in a straightforward manner. The starting material 1t was not soluble in acetonitrile, but performing the reaction in water allowed the formation of 2t in an 81% yield.…”
Section: Resultsmentioning
confidence: 99%
“…58 However, human PRTs have very low tolerance for substrate variation and cannot be used to incorporate unnatural nucleobases. This was shown by Pfefferkorn and Pfefferkorn in an early study with tritium-labeled uridine and uracil, where it was demonstrated that human cells could incorporate 3 H-uridine via nucleotide salvage pathways, but not 3 H-uracil. 59 In contrast, the parasite Toxoplasma gondii 4B), whereas unmodified HeLa cells did not.…”
Section: Cell-type-specific Rna Metabolic Labelingmentioning
confidence: 78%
“…The compatibility of the cells expressing the mutant TgUPRT and treatment with 5VU was studied by the MTT cell metabolic activity assay, and no significant difference between treated and untreated cells was observed. 3 With these results, we demonstrated cell-specific RNA metabolic labeling via the use of 5-VU and a triple-mutant TgUPRT, overcoming the nonspecific incorporation challenges faced with wild-type TgUPRT.…”
Section: Nonspecific Incorporation Of Uracil Nucleobasesmentioning
confidence: 82%
See 1 more Smart Citation
“…A major limitation with chemical approaches to track RNA expression is the inability to tag RNAs from cell types of interest. Expression of exogenous enzymes (Figure a) that, when paired with modified nucleosides/nucleobases, can enable cell-specific metabolic labeling of RNA. However, each of these methods relies on expression of an exogenous enzyme, which requires laborious procedures to produce expression constructs; further, the utilization in living animals takes extensive time to implement. Overall, these limitations suggest additional methods need to be explored for cell-specific metabolic labeling of RNA, but may also present an opportunity for more sophisticated chemical approaches toward this problem.…”
mentioning
confidence: 99%